Hyperacute stroke and the specialist nursing impact: exploring the cause and context of feelings of secondary traumatic stress – a qualitative inquiry. (June 2022) - Wilkinson, Mark; Cox, Nigel; Witham, Gary; Haigh, Carol
Background: Secondary traumatic stress (STS) has been defined as the stress resulting from helping or wanting to help a traumatised or suffering person. The hyperacute nature of stroke specialist nurses' work places them at risk of developing STS. Aims: To explore the factors that are influential in stroke specialist nurses' experience of STS development within hyperacute practice. Methods: This study is qualitative with a narrative design. Data were collected from a purposive sample of stroke specialist nurses (20 female and 2 male) working in hyperacute services during the years 2016 and 2017. Data were analysed using Polkinghorne's approach. Results: This research identified four themes: exposure to acute suffering and death- young presentations; moral distress; interactions with relatives and problematic healthcare systems. Conclusion: The findings from this study suggest that stroke specialist nurses are exposed to multiple triggers which are commensurate with the potential for STS development. The findings contribute a new understanding of the emotional burden of hyperacute specialist stroke nursing that has implications for patient safety and satisfaction, services provision and staff well-being.